Controllable superhydrophobic aluminum surfaces with tunable adhesion fabricated by femtosecond laser. (June 2018) - Song, Yuxin; Wang, Cong; Dong, Xinran; Yin, Kai; Zhang, Fan; Xie, Zheng; Chu, Dongkai; Duan, Ji'an
Highlights: A effective method is proposed for fabricating superhydrophobic Al surfaces. Laser parameters influence water droplets' rebound behavior on treated surfaces. The tunable adhesion of the laser-ablated surfaces is studied. Potential application of the superhydrophobic surfaces has been presented. Abstract: In this study, a facile and detailed strategy to fabricate superhydrophobic aluminum surfaces with controllable adhesion by femtosecond laser ablation is presented. The influences of key femtosecond laser processing parameters including the scanning speed, laser power and interval on the wetting properties of the laser-ablated surfaces are investigated. It is demonstrated that the adhesion between water and superhydrophobic surface can be effectively tuned from extremely low adhesion to high adhesion by adjusting laser processing parameters. At the same time, the mechanism is discussed for the changes of the wetting behaviors of the laser-ablated surfaces. These superhydrophobic surfaces with tunable adhesion have many potential applications, such as self-cleaning surface, oil–water separation, anti-icing surface and liquid transportation.